2004
DOI: 10.1889/1.1811443
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency drive of high‐Xe‐content PDPs for high efficiency and low‐voltage performance

Abstract: Abstract— It has been well known that the luminous efficiency of PDPs can be improved by increasing the Xe content in the panel. For instance, the efficiency is improved by a factor 1.7 when the Xe content is increased from 3.5% to 30%. The sustain pulse voltage, however, increases from 180 to 230 V by a factor 1.3. It was found that the increase in the sustain pulse voltage can be suppressed by increasing the sustain pulse frequency. The high‐frequency operation further increases the luminous efficiency. If t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Apart from higher sustain voltages, a fast discharge development can be stimulated by other design or driving characteristics. For instance, by an adapted capacitive cell design, a special sustain waveform or a high sustain frequency [14]- [16]. In all cases, a correspondence between a fast discharge development and high discharge efficiency is found.…”
Section: A Power Input and Discharge Efficiencymentioning
confidence: 98%
See 1 more Smart Citation
“…Apart from higher sustain voltages, a fast discharge development can be stimulated by other design or driving characteristics. For instance, by an adapted capacitive cell design, a special sustain waveform or a high sustain frequency [14]- [16]. In all cases, a correspondence between a fast discharge development and high discharge efficiency is found.…”
Section: A Power Input and Discharge Efficiencymentioning
confidence: 98%
“…This condition is denoted as the high efficiency mode. The high efficiency mode is normally observed for higher sustain voltages 200 V at 50 kHz sustain frequency, but the high efficiency mode region can be stretched to lower voltages for higher sustain frequency operation [16].…”
Section: A Power Input and Discharge Efficiencymentioning
confidence: 99%
“…Also under a fast discharge build-up condition the electron-heating efficiency increases, due to a decrease of the ion heating losses in the cathode sheath [5]. The high efficiency mode is usually found for sustain voltages >200V at a sustain frequency of 50 kHz, but the high efficiency mode region can be stretched to lower voltages for higher frequency operation [6]. The dotted line in FIG.…”
Section: Methodsmentioning
confidence: 97%
“…Our experimental result has shown that, in the case of the sustain discharge gap larger than the barrier rib height, the luminous efficiency can vary depending on the operating frequency, which has not been reported yet. Even though the effect of the operating frequency on the conventional short-discharge-gap case(discharge gap < barrier rib height) has been previously reported, it is not directly applicable to the wide-gap-discharge characteristics on the operating frequency [9], [10]. Fig.…”
Section: Methodsmentioning
confidence: 99%